Willingness to pay for colorectal cancer screening: A systematic review - Afifa Naila Nabila, Susi Ari Kristina (Journal of Applied Pharmaceutical Science, 2024)
Colorectal cancer (CRC) screening is crucial to reduce the global economic burden related to CRC. The purpose of this study is to examine studies on assessing willingness to Pay (WTP) for CRC screening and to investigate any potential variables influencing WTP. A systematic review was conducted through databases in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline. The study included 10 English-language studies that evaluated WTP for CRC screening. The study assessed how much participants were willing to pay for the assumed test cost by calculating the proportion of their WTP value. All values were converted to 2023 USD using a consumer price indices calculator and US Treasury converter. This study showed that the WTP value for CRC screening varied from USD 11.07 to USD 658.65. The co-payment rate ranged from 0.15 to 83.73. The factors influencing WTP value includes sociodemographic factors and the screening test attributes. Our study revealed the variative relationship between sociodemographic parameters and test features in influencing individuals’ decisions about CRC screenings. Understanding the importance of both demographic factors and test attributes is crucial for future research to develop targeted strategies for improving CRC screening uptake. Additionally, insights into WTP value aid in shaping public policies for CRC screening programs.
Keywords: Willingness-to-pay, colorectal cancer, screening, health economic, systematic review